C34T mutation of the AMPD1 gene in an elite white runner - Lucia, A.; Martin, M. A.; Esteve-Lanao, J.; San Juan, A. F.; Rubio, J. C.; Olivan, J.; Arenas, J. (British Journal of Sports Medicine, 2006)
The case is reported of an elite, male, white endurance runner (28 years of age), who is one of the best non-African runners in the world despite carrying the C34T mutation in the gene (AMPD1) that encodes the skeletal muscle specific isoform of AMP deaminase, an enzyme that plays an important role in muscle metabolism. The frequency of the mutant allele in sedentary white people is 8-11%. Previous research has shown that this mutation, at least in homozygotes, can impair the exercise capacity of untrained people and their trainability. The maximum oxygen uptake of the study subject was exceptionally high (83.6 ml/kg/min), whereas his ammonia and lactate concentrations at high submaximal running speeds were lower than those of other world class runners who are not carriers of the mutation. The partial metabolic deficiency of the study subject is possibly compensated for by his exceptionally favourable anthropometric characteristics (body mass index 18.2 kg/m2).